Mimbar Hadis dan Kultum untuk Membangun Kesadaran Religius Masyarakat Desa Bonto Lojong, Kabupaten Bantaeng - Ridwan; Sirajuddin; Imran (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
Bonto Lojong village has a status as a definitive village and is classified as a self-help village, including a village that is quite potential, developed and open. However, religious activities are not very lively, so this becomes the basis for the implementation of PKM STIBA Makassar. To identify problems that occur in the community, map problems, the needs of the da'wah movement, and develop strategies for the preparation of KKN programs, soar analysis is used with the results obtained; Strenght: muntea village, Bonto Lojong village, Uluere sub-district and Sunggumanai sub-village Pa'jukukang Pa'jukukang subdistrict Bantaeng 100% Muslim, and open-minded, and STUDENTS STIBA Makassar has been equipped with good religious understanding, has da'wah skills; Oppurtunities: support and cooperation of apparat villages and communities; Aspiration: stakeholders facilitate the community to obtain its spiritual needs; Result: people become more understanding of their religion well. The results of this analysis Realize kultum activities and hadith readings. After the existence of this program, people began to be interested to listen to the reading of hadith and kultum delivered by students of KKN STIBA Makassar. This will certainly add insight to the Islamic congregation of the mosque.